THERMOPLASTIC RESIN COMPOSITION - YAMAUCHI SHINICHI; NAKANO HIROSHI (1993)
PURPOSE:To obtain the subject composition excellent in heat resistance, mechanical strength and moldability, etc., by incorporating a cross-linking agent in a resin comprising a specific unsaturated copolymer and polyphenylene ether resin. CONSTITUTION:The objective composition can be obtained by incorporating 100 pts.wt. of a resin comprising (A) 10-90wt.% of an unsaturated copolymer 0.01-50mol (based on the component (2)) in the unit concentration produced by copolymerization between (1) a 2-8C alpha-olefin (pref. ethylene or propylene) and (2) a 4-5C diene compound (pref. 4-methyl-1,4-hexadiene) and (B) 90-10wt.% of a polyphenylene ether resin with (C) 0.01-10 pts.wt. of a cross-linking agent (pref. N,N'-m-phenylenebismaleimide).